Impact of External Ventricular Drainage Volumes on Shunt Dependency after Subarachnoid Hemorrhage - Hayek, Muhammad Ali; Roth, Christian; Kaestner, Stefanie; Deinsberger, Wolfgang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background The indication for and the timing of a permanent shunt operation in patients following acute hydrocephalus (HC) after subarachnoid hemorrhage (SAH) remains controversial because risk factors for chronic HC fail to predict permanent shunt dependency. The amount of cerebrospinal fluid (CSF) drained via an external ventricular drain (EVD) may predict shunt dependency.Methods We conducted a retrospective study of our HC database from January 2006 to December 2011. All patients receiving an EVD due to acute HC after SAH were analyzed. The daily amount of drained CSF was documented until the EVD was removed or converted to a permanent shunt either immediately or during a follow-up period of 6 months.Results A total of 139 patients (48 male, 91 female; mean age: 57 ± 14 years) were eligible for the study. Mean duration of EVD was 16 ± 10 days (range: 4–60 days). A permanent shunt was necessary in 32% of cases (n = 45). The mean daily CSF volume was 139 ± 17 mL (range: 15–460 mL). Using repeated-measures analysis of variance, there was a significant difference of daily drained CSF volumes between both the groups in the first 15 days after the EVD.Conclusion Our results suggest that the daily amount of external CSF drainage volume in the acute state of SAH might influence the development of HC.
Keywords: hydrocephalus; subarachnoid hemorrhage; shunt; ventricular drainage; CSF